Highly Conjugated Graphitic Carbon Nitride Nanofoam for Photocatalytic Hydrogen Evolution - Cheng, Chuan-Qi; Feng, Yi; Shi, Zi-Zheng; Zhou, Yun-Long; Kang, Wen-Jing; Li, Zhe; Mao, Jing; Shen, Gu-Rong; Dong, Cun-Ku; Liu, Hui; Du, Xi-Wen (Langmuir, 2022)
As a metal-free photocatalyst, graphitic carbon nitride (g-CN) shows great potential for photocatalytic water splitting, although its performance is significantly limited by structural defects due to incomplete polymerization. In the present work, we successfully synthesize highly conjugated g-CN nanofoam through an iodide substitution technique. The product possesses a high polymerization degree, low defect density, and large specific surface area; as a result, it achieves a hydrogen evolution rate of 9.06 mmol h–1 g–1 under visible light irradiation, with an apparent quantum efficiency (AQE) of 18.9% at 420 nm. Experimental analysis and theoretical calculations demonstrate that the recombination of photogenerated carriers at C–NH x defects was effectively depressed in the nanofoam, giving rise to the high photocatalytic activity.